2012
DOI: 10.1101/lm.027359.112
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb α2-adrenoceptor activation promotes rat pup odor-preference learning via a cAMP-independent mechanism

Abstract: In this study, three lines of evidence suggest a role for a 2 -adrenoreceptors in rat pup odor-preference learning: olfactory bulb infusions of the a 2 -antagonist, yohimbine, prevents learning; the a 2 -agonist, clonidine, paired with odor, induces learning; and subthreshold clonidine paired with subthreshold b-adrenoceptor activation also recruits learning. Increased mitral cell layer pCREB occurs with clonidine-infusion, but cAMP is not increased. Similar results using a GABAa-antagonist suggest that disinh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For example, both natural and learned odors produce a similar enhancement of OB responding during the sensitive-period, which has been assessed through a variety of techniques including 2-deoxy-glucose (2-DG) uptake, c-Fos immunoreactivity (ir), CREB phosphorylation, electrophysiology, and optical imaging (205208, 211214). Thus, olfactory-based attachment learning in neonatal rats is associated with the acquisition of odor-specific neural changes in the OB, which can only be acquired during the sensitive-period, and are retained throughout development (111, 201, 215218).…”
Section: Neurobiology Of Infant-attachment and The Role Of The Hpa-axmentioning
confidence: 99%
“…For example, both natural and learned odors produce a similar enhancement of OB responding during the sensitive-period, which has been assessed through a variety of techniques including 2-deoxy-glucose (2-DG) uptake, c-Fos immunoreactivity (ir), CREB phosphorylation, electrophysiology, and optical imaging (205208, 211214). Thus, olfactory-based attachment learning in neonatal rats is associated with the acquisition of odor-specific neural changes in the OB, which can only be acquired during the sensitive-period, and are retained throughout development (111, 201, 215218).…”
Section: Neurobiology Of Infant-attachment and The Role Of The Hpa-axmentioning
confidence: 99%
“…Several lines of evidence have suggested that neuromodulator norepinephrine (NE) is critical in early odor preference learning and it serves as a UCS signal in this model. NE is released from the locus coeruleus (LC) following tactile stimulation ( Nakamura et al, 1987 ; Nakamura and Sakaguchi, 1990 ; Rangel and Leon, 1995 ) and pharmacological blocking of either α- or β-adrenoceptors in the olfactory bulb (OB; Sullivan et al, 2000b ; Shakhawat et al, 2012 ), or the anterior piriform cortex (aPC; Morrison et al, 2013 ), prevents early odor preference learning in rat pups. Additionally, odor preference learning can be acquired when a novel odor is paired with α- or β-adrenoceptor activation ( Sullivan et al, 2000b ; Harley et al, 2006 ; Morrison et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced release of noradrenaline (NA) within the MOB plays an important role in long-term synaptic plasticity and odor learning in a variety of contexts. These include olfactory conditioning in neonatal rats (Sullivan et al 1989(Sullivan et al , 1992(Sullivan et al , 2000Harley et al 2006;Zhang et al 2010;Shakhawat et al 2012), the learning of newborn lamb odors after parturition in sheep (Pissonnier et al 1985), odor discrimination after memory formation in mice (Doucette et al 2007;Shea et al 2008;Moreno et al 2012), a specific long-term suppression of mitral cell (MC) responses to paired odors in mice (Shea et al 2008), a long-term reduction of paired-pulse inhibition in neonatal rats (Wilson and Leon 1988), long-term enhancement of synchronized γ frequency oscillations in rat MOB slices (Gire and Schoppa 2008;Pandipati et al 2010), long-term potentiation (LTP) of synaptic strength in rat MOB slices (Yuan 2009;Zhang et al 2010), and a long-term suppression of presynaptic input to MCs in mice (Eckmeier and Shea 2014).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%